A comparative study on basophil activation test, histamine release assay, and passive sensitization histamine release assay in the diagnosis of peanut allergy. Issue 1 (10th August 2017) - Larsen, L. F.; Juel‐Berg, N.; Hansen, K. S.; Clare Mills, E. N.; van Ree, R.; Poulsen, L. K.; Jensen, B. M.
Abstract: Background: Allergy can be diagnosed using basophil tests. Several methods measuring basophil activation are available. This study aimed at comparing basophil activation test (BAT), histamine release assay (HR), and passive sensitization histamine release assay (passive HR) in the diagnosis of peanut allergy. Methods: BAT, HR, and passive HR were performed on 11 peanut‐allergic and 14 nonallergic subjects. Blood was incubated with peanut extract or anti‐IgE and tests were performed as follows: BAT—CD63 upregulation was assessed by flow cytometry; HR—released histamine was quantified by a glass fiber‐based fluorometric method; passive HR—IgE‐stripped donor basophils were incubated with participants' serum and histamine release was quantified as HR. Results: CDsens, a measure of basophil allergen sensitivity, was significantly higher for BAT (80.1±17.4) compared to HR (23.4±10.31) and passive HR (11.1±2.0). BAT, HR, and passive HR had a clinical sensitivity of 100%, 100%, and 82% and specificity of 100%, 100%, and 100%, respectively, when excluding inconclusive results. BAT identified 11 of 11 allergic patients, HR 10, and passive HR 9. Likewise, BAT recognized 12 of 14 nonallergic subjects, HR 10, and passive HR 13. However, the tests' diagnostic performances were not statistically different. Interestingly, nonreleasers in HR but not in BAT had lower basophil count compared to releasers (249 vs 630 counts/min). Conclusion: BAT displayed a significantly higher CDsens compared to HR and passive HR. The basophil tests' diagnostic performances were not significantly different. Still, BAT could diagnose subjects with low basophil number in contrast to HR.